Status and Analysis of Scientific Journals Indexed in SCI, SCI-E and SSCI Citation Databases from Romania and Serbia. (2015) - Dašić, Predrag; Moldovan, Liviu; Grama, Lucian
Abstract: SCI, SCI-E and SSCI are one of the major citation databases (CDB) in the world in the field of natural, applied scientific disciplines and social sciences. Therein recorded are the data of scientific journals and their ranking in over 80 countries worldwide. This paper presents an analysis of scientific journals indexed in SCI, SCI-E and SSCI citation databases (CDB) from Romania and Serbia for the period 1998-2012. The study reveals some similarities in the two countries with similar approaches for the valorisation of research, which is much more oriented for international visibility by indexing in relevant databases. For the moment a saturation limit has been reached for the number of indexed scientific journals in SCI, SCI-E and SSCI citation databases, which needs elaboration of new strategies in order to increase the number of indexed publications and their impact factor.